1996
DOI: 10.1149/1.1837052
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Electrochromic Coatings: Composites of Polyaniline and Polyacrylate‐Silica Hybrid Sol‐Gel Materials

Abstract: A low-cost technique for fabricating large-area electrochromic coatings is described. Polyaniline was incorporated into polyacrylate-silica hybrid sol-gel networks using suspended particles or solutions. A solution of polyaniline and poly[methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylatel can be spray-or brush-coated on transparent indium-tin oxide substrates to form robust electrochromic coatings. Silane functional groups on the polyacrylate chain act as coupling and cross-linking agents to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…40 For example, electrochemically deposited poly(diphenylbenzidine) films have been reported to be easily detached from the ITO electrode upon potential cycling. 30 Furthermore, silanized polyaniline, 41 amino-silanized glass, 39 and conducting polymer composites 38,[42][43][44][45][46] have been employed to promote the surface adhesion of electrodeposited and solution-cast films. For example, Wei et al have recently demonstrated the durability of large-area electrochromic coatings based on composites of polyaniline and polyacrylatesilica hybrid sol-gel materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 For example, electrochemically deposited poly(diphenylbenzidine) films have been reported to be easily detached from the ITO electrode upon potential cycling. 30 Furthermore, silanized polyaniline, 41 amino-silanized glass, 39 and conducting polymer composites 38,[42][43][44][45][46] have been employed to promote the surface adhesion of electrodeposited and solution-cast films. For example, Wei et al have recently demonstrated the durability of large-area electrochromic coatings based on composites of polyaniline and polyacrylatesilica hybrid sol-gel materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wei et al have recently demonstrated the durability of large-area electrochromic coatings based on composites of polyaniline and polyacrylatesilica hybrid sol-gel materials. [42][43][44][45][46] In this paper, a new series of electrochromic poly (3-HT-co-3TPP)-silica hybrid materials was developed, in which the structure of the conjugated P3HT network was modified through the formation of copolymer poly(3HT-co-3TPP), which contained a tunable sulfur/nitrogen ratio and a sol-gel precursor. The electrochromic performance of poly(3HT-co-3TPP)-silica hybrid materials relative to pure P3HT on indium-tin-oxide (ITO)-coated electrode and microslide was evaluated in electrochemical cyclic voltammetry (CV) studies.…”
Section: Introductionmentioning
confidence: 99%
“…There are several research articles reporting that the capacity of pure spinel LiMn 2 O 4 diminishes at high reduction levels [6,7]. The capacity fading of lithiated transition metal oxides such as LiCoO 2 , LiNiO 2 and LiMn 2 O 4 occurs due to various factors such as Jahn-Teller distortion (change of a cubic symmetry into tetragonal one, a two-phase unstable reaction), slow dissolution of manganese into the electrolyte [8], lattice instability [9] and particle-size distribution [10,11]. To suppress the Jahn-Teller distortion and obtain high cycling capacity, many researchers have studied Li-Mn-O spinels in order to improve cycleability by partially chemical substitution of Mn 3+ with various divalent, trivalent and tetravalent-doped cations such as Sm, Co, Zn, Ca, Fe, Ni, Cd, Tb, Ga, Ti, Al, V and Cr [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al synthesized PANI/polyacrylate-silica (SiO 2 ) composite films with enhanced surface adhesion for largearea EC applications [17]. Deepa et al reported high optical contrast of PANI thin films derived from ionic liquid/polyethylene glycol by electrodeposition [18].…”
Section: Introductionmentioning
confidence: 99%